Genetic features of the marine polychaete Sirsoe methanicola from metagenomic data - Lim, Shen Jean; Thompson, Luke R.; Goodwin, Kelly D. (Frontiers in Marine Science, 2023)
The methane ice worm Sirsoe methanicola is the only marine polychaete species observed to colonize the methane hydrates of the Gulf of Mexico. Methane hydrates are ephemeral features of deep-sea cold seeps, and finding worm-colonized hydrates is rare; thus, little is known about these organisms. Recent metagenomic analysis predicted prokaryotic taxa and pathways from S. methanicola gut contents and worm fragments. Here, we increase the genetic information known about S. methanicola by assembling its nuclear rRNA genes (18S rRNA and 28S rRNA), mitochondrial genome (mitogenome), and other protein-coding genes from metagenomic data. Assembled 18S rRNA and 28S rRNA gene sequences of S. methanicola were near-identical to previously reported S. methanicola sequences. The 17,403-bp mitogenome of S. methanicola is the first mitogenome sequence of the family Hesionidae, consisting of 39.03% G+C content, 13 protein-coding genes, 24 tRNAs (including two split trnM genes), and 2 rRNA genes. Protein-coding genes in the S. methanicola metagenomes assigned to the phylum Annelida were involved in cell adhesion, signaling, ubiquitin system, metabolism, transport, and other processes. From the metagenomes, we also found 42 homologs of the cytochrome P450 (CYP) superfamily putatively involved in polycyclic aromatic hydrocarbon (PAH) metabolism. Our results encourage further studies into the genetic adaptations of S. methanicola to its methane hydrate habitat, especially in the context of deep-sea ecology and nutrient cycling.